Efek pemberian beberapa jenis antikoagulan sebagai profilaksis sindrom pasca trombotik setelah DVT (systematic literature review) - Ida Bagus Yudharma Indraharsanae; Ketut Putu Yasa (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
This study aimed to evaluate the efficacy of several types of anticoagulants—VKA, LMWH, and DOAC in preventing PTS after DVT through a systematic literature review. The method used involved secondary data search from databases such as PubMed, ScienceDirect, and Google Scholar between 2013–2024, with inclusion criteria including randomized clinical trials and related observational studies. The results showed that DOAC, especially rivaroxaban, significantly reduced the incidence and severity of PTS compared to VKA, with a lower risk of severe PTS. LMWH also showed positive results, although head-to-head evidence with DOAC is still limited. These findings suggest that the type and duration of anticoagulant therapy play an important role in preventing PTS, and encourage the need for further research, especially RCTs between LMWH and DOAC.